Wykorzystanie miary Braya-Curtisa do oceny zmian w innowacyjności europejskiej przestrzeni regionalnej - Markowska, Małgorzata (The Implementation of Bray-Curtis Measure for the Assessment on Changes Occurring in the Innovation of European Regional Space, 2008)
The article presents the procedure based on Bray-Curtis distance measure which allows for the grouping of regions into sets characterized by different intensity of changes in the values of characteristics selected for the description of a complex phenomenon. The suggested scheme was applied for the assessment of changes intensity in time in regional innovation. There were defined homogenous groups of regions at NUTS-2 level in the European Union with reference to the scale of changes in values related to the suggested innovation measures. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 6, s. 17-25